If you lived at the time of Martin Luther King - Levine, Ellen; Rich, Anna, 1956- (New York : Scholastic, 1994)
This book focuses on the Civil Rights Movement of the 1950s and 1960s. Full-color art and an engaging question-and-answer format help children learn what it was like to participate in the Montgomery Bus Boycott, stage a sit-in at a lunch counter, join the famous March on Washington, and more.
G6
Keywords: King, Martin Luther, -- Jr., -- 1929-1968 -- Juvenile literature; King, Martin Luther, -- Jr., -- 1929-1968.; African Americans -- Civil rights -- History -- 20th century -- Juvenile literature; Civil rights movements -- United States -- History -- 20th century -- Juvenile literature; African Americans -- Civil rights; United States -- Race relations -- History -- 20th century -- Juvenile literature; United States -- Race relations -- History